Răspuns :
b-a=10 ⇒ b = 10 +a
c-1=46a ⇒ c = 46a + 1
a + b+ c = 155
⇒ a + ( 10 +a ) + ( 46a + 1 ) = 155
48a + 11 = 155
48a = 155 - 11
48a = 144
a = 144 : 48 = 3
deci : a = 3
b = 10 + 3 = 13
c = 46 · 3 + 1 = 138 + 1 = 139
c-1=46a ⇒ c = 46a + 1
a + b+ c = 155
⇒ a + ( 10 +a ) + ( 46a + 1 ) = 155
48a + 11 = 155
48a = 155 - 11
48a = 144
a = 144 : 48 = 3
deci : a = 3
b = 10 + 3 = 13
c = 46 · 3 + 1 = 138 + 1 = 139
[tex]b-a=10=\ \textgreater \ b=10+a \\ c-1=46a=\ \textgreater \ c=46a+1 \\ a+10+a+46a+1=155 \\ 48a=155-11 \\ a=144:48=\ \textgreater \ a=3 \\ b=10+3=13 \\ c=46*3+1=\ \textgreater \ c=139[/tex]